SEMIOTIC ANALYSIS IN ADVERTISING: HOW MESSAGES ARE COMMUNICATED TO SOCIETY - Mohamad Sudi (Jurnal Komunikasi, 2024)
Any communication that aims to persuade someone to buy a product or service, encourage public opinion, or garner support for an advertiser's viewpoints or actions is considered advertising. Information can be communicated effectively and efficiently through advertising. This can be used to influence individuals to use the advertised goods and services. Through a semiotic theory approach, advertisements are expected to be able to be classified based on the signs, codes and meanings contained therein. A review of the literature was the method employed in this article. Library research involves gathering information and data from a variety of sources found in libraries, including reference books, published works, notes, articles, and journals that are relevant to the issue you are trying to address. This research discusses communication theory, the meaning of advertising, semiotics in the context of advertising, the dynamics of messages in advertising, and semiotic models